Beyond Kozeny-Carman: Predicting the Permeability in Porous Media - Schulz, Raphael; Ray, Nadja; Zech, Simon; Rupp, Andreas; Knabner, Peter (Transport in Porous Media, 2019)

Coupling scales in process-based soil organic carbon modeling including dynamic aggregation - Zech, Simon; Prechtel, Alexander; Ray, Nadja (Journal of Plant Nutrition and Soil Science, 2024)
Background: Carbon storage and turnover in soils depend on the interplay of soil architecture, microbial activities, and soil organic matter (SOM) dynamics. For a fundamental understanding of the mechanisms that drive these processes, not only the exploitation of advanced experimental techniques down to the nanoscale is necessary but also spatially explicit and dynamic image-based modeling at the pore scale. Aim: We present a modeling approach that is capable of transferring microscale information into macroscale simulations at the profile scale. This enables the prediction of future developments of carbon fluxes and the impact of changes in the environmental conditions linking scales. Method: We consider a mathematical model for CO2 transport across soil profiles (macroscale), which is informed by a pore-scale (microscale) model for C turnover. It allows for the dynamic, self-organized re-arrangement of solid building units, aggregates and particulate organic matter (POM) based on surface interactions, realized by a cellular automaton method, and explicitly takes spatial effects on POM turnover such as occlusion into account. We further include the macroscopic environmental conditions water saturation, POM content, and oxygen concentration. Results: The coupled simulations of macroscopic transport and pore-scale carbon and aggregate turnover reveal the complex, nonlinear interplay of the underlying processes. Limitations by diffusive transport, oxygen availability, texture-dependent occlusion and turnover of OM drive CO2 production and carbon storage. Conclusions: This emphasizes the need for such micro–macro models exchanging information on different scales to investigate and quantify the effects of structural changes, variations in environmental conditions, or degradation processes on carbon turnover.
CRIS-Team Scopus Importer:2024-01-26
Keywords: carbon turnover; cellular automaton method; diffusion equation mechanistic image-based modeling; pore-scale model; soil structure dynamics; upscaling

Explicit spatial modeling at the pore scale unravels the interplay of soil organic carbon storage and structure dynamics - Zech, Simon; Schweizer, Steffen A.; Bucka, Franziska B.; Ray, Nadja; Kögel-Knabner, Ingrid; Prechtel, Alexander (Global Change Biology, 2022)
The structure of soil aggregates plays an important role for the turnover of particulate organic matter (POM) and vice versa. Analytical approaches usually do not disentangle the continuous re-organization of soil aggregates, caught between disintegration and assemblage. This led to a lack of understanding of the mechanistic relationship between aggregation and organic matter dynamics in soils. In this study, we took advantage of a process-based mechanistic model that describes the interaction between the dynamic (re-)arrangement of soil aggregates, based on dynamic image analysis data of wet-sieved aggregates, to analyze the turnover of POM, and simultaneous soil surface interactions in a spatially and temporally explicit way. Our novel modeling approach enabled us to unravel the temporal development of aggregate sizes, organic carbon (OC) turnover of POM, and surface coverage as affected by soil texture, POM input, and POM decomposition rate comparing a low and high clay soil (18% and 33% clay content). Our results reveal the importance of the dynamic re-arrangement of soil structure on POM-related turnover of OC in soils. Firstly, aggregation was largely determined by the POM input fostering aggregates through additional gluing joints outweighing soil texture at lower decomposition rate, whereas at higher decomposition rate, soil texture had a higher influence leading to larger aggregates in the high clay soil. Secondly, the POM storage increased with clay content, showing that surface interactions may delay the turnover of OC into CO2. Thirdly, we observed a structural priming effect in which the increased input of POM induced increased structural re-arrangement stimulating the mineralization of old POM. This work highlights that the dynamic re-arrangement of soil aggregates has important implications for OC turnover and is driven by underlying surface interactions where temporary gluing spots stabilize larger aggregates.
Created from Fastlane, Scopus look-up
Keywords: aggregates; clay content; OC turnover; POM degradation; soil structure dynamics; soil surface interactions; spatially explicit modeling; structural priming effect

How water connectivity and substrate supply shape the turnover of organic matter – Insights from simulations at the scale of microaggregates - Zech, Simon; Ritschel, Thomas; Ray, Nadja; Totsche, Kai Uwe; Prechtel, Alexander (Geoderma, 2022)
Microaggregates are hot spots of microbial activity at a scale that frequently poses a severe experimental challenge or defies a direct observation. Mathematical models that combine the mechanisms of spatially resolved organic matter transport with the processes of organic matter turnover can facilitate the understanding of soil microbial dynamics and the function of soils at these scales. In this study, we investigate microbial population dynamics and the turnover of particulate organic matter (POM) in soil microaggregates. CT images of microaggregates obtained from samples of natural soils serve as basis for selecting the simulation domain. For different levels of water saturation, the fluid (liquid and gas) distribution within the pore space is calculated according to a morphological model. We consider bacteria and POM, which are heterogeneously distributed within the liquid phase. Dissolved organic carbon (DOC) is released by hydrolyzing POM, assuming a reaction following first-order kinetics. DOC spreads by diffusion and can subsequently be consumed by bacteria and turned into CO2. The growth of bacteria is realized by a cellular automaton framework (CAM) and based on Michaelis–Menten kinetics due to the uptake of DOC. Our simulations show that the heterogeneous distribution of substrate and bacteria results in an overall biodegradation kinetics and CO2 output that strongly depends on the microaggregate scale (<250μm). Only very specific cases can be distinguished globally, e.g., when the substrates are isolated from bacteria due to a disconnected liquid phase. Locally, however, heterogeneities in substrate distribution impact the development of bacteria populations, e.g., a smaller geodesic distance of bacteria to the substrate promotes bacterial growth locally.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Cellular automaton; Dissolved organic matter; Michaelis–Menten kinetics; Microbial habitats; X-ray microtomography

Microaggregation of goethite and illite evaluated by mechanistic modeling - Zech, Simon; Dultz, Stefan; Guggenberger, Georg; Prechtel, Alexander; Ray, Nadja (Applied Clay Science, 2020)
Clay minerals and Fe- and Al-oxyhydroxides are considered as the most important materials for the formation of microaggregate building units in soils. The mode of aggregation and the resulting structure and stability are largely determined by their size, aspect ratio (AR), differences in surface charge (SC), and mixing ratio. Here, the impact of these parameters on the formation of microaggregate building units (BUs) was elucidated with a mechanistic model, i.e. using a twophase cellular automaton method, in which prototypes of illite and goethite were implemented. The simulations allowed assessing the formation of particle arrangements during aggregation, moreover building unit diameters, and the number of discrete particles. The contact area between particles was evaluated as a quantitative measure for stability. Homoaggregation of illite under the sole influence of attracting van der Waals forces enabling face-to-face as well as edge-to-face contacts, resulted in compact structures with a small mean diameter and specific surface area. In contrast, electrostatic attraction between negatively charged faces and positively charged edges favored formation of larger card-house structures, where low contact areas indicated the low stability of the resulting BUs. At constant AR, homoaggregation of illite of different particle size led to BUs of different stability, more precisely smaller particle sizes led to more stable BUs. Variation of the AR of illite, while keeping the particle size constant, revealed that most stable BUs arose from illite with smallest AR. Shielding of coarse goethite particles due to attachment of fine illite with negatively charged edges increased the number of discrete fine illite particles not aggregated. Aggregation of illite with positively charged edges was in fundamental difference to results from simulations with negative edges because of electrostatic attraction between illite particles. The simulation setting, without using fitting parameters resulted in an appropriate approximation of laboratory findings. The simulation clearly facilitated the understanding of microaggregate building unit formation and stability by illuminating turnover dynamics and provision of quantitative data.
Created from Fastlane, Scopus look-up
Keywords: Aspect ratio; Cellular automaton; Goethite; Illite; Mechanistic modeling; Microaggregate building units

Numerical investigations of degenerate equations for fluid flow and reactive transport in clogging porous media - Zech, Simon; Ray, Nadja; Schulz, Raphael (Journal of Mathematical Analysis and Applications, 2022)
Structural changes of the pore space and clogging phenomena are inherent to many porous media applications. However, numerical investigations of the related flow and transport problem remain challenging due to the degeneration of the hydrodynamic parameter porosity, and in turn of the permeability and diffusion tensor. A remedy is to use appropriate scalings of the unknowns velocity, pressure and species' concentration in terms of the porosity. This enables us to conduct numerical simulations for the combined, degenerating flow and transport problem. As discretization method, lowest order mixed finite elements are used and stability of the numerical scheme is shown. Under certain additional regularity assumptions, convergence (with optimal order) can be proven. Our numerical results confirm that optimal convergence is obtained for the transformed variables whereas the non-transformed variables might not converge.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Clogging; Degenerate PDEs; Error analysis; Mixed finite elements; Porous media